Clinical Value of Systemic Immune Inflammation and Pan-Immune Inflammation in Adenoid Hypertrophy - Tuğba Yemiş; Mehmet Birinci; Metin Çeliker; Gökçe Aydın Balaban; Erdal Eren Askeroğlu; Özlem Çelebi Erdivanlı (Galenos Yayinevi, 2024)
Aim: This study aimed to investigate the relationship between adenoid hypertrophy, the most common cause of obstructive sleep apnea (OSA) in children, with the systemic immune inflammation index (SII) and the pan-immune inflammation value (PIV), and to evaluate the clinical utility of SII and PIV in prognostic and predictive aspects. Materials and Methods: The retrospective data from 29 patients presenting to the otorhinolaryngology clinic with dyspnea and undergoing adenoidectomy for OSA between June, 2022 and June, 2023 were reviewed. Thirty age- and sex-matched healthy subjects were included as the control group. The preoperative and postoperative 6-month SII and PIV values of both groups were compared. Results: There was no significant difference between the groups in terms of age and gender (p>0.05). Platelet SII and PIV were statistically significantly higher in patients in the preoperative period compared to the control group (p<0.05). No significant differences were found in the preoperative neutrophil, lymphocyte, and monocyte counts between the patients and the control subjects (p>0.05). Postoperative neutrophil, platelet, and monocyte counts, as well as the SII and PIV values of the patients, were significantly higher than of those in the control group (p<0.05). Conclusion: Our study highlights the potential utility of SII and PIV in assessing systemic inflammation in adenoid hypertrophy-related OSA. However, the unexpected increase in postoperative SII and PIV values underscores the need for further research into their clinical implications.